2017
DOI: 10.11606/issn.1984-4867.v28i2p224-244
|View full text |Cite
|
Sign up to set email alerts
|

Choosing a Restaurant: important attributes and related features of a consumer’s decision making process

Abstract: A correta identificação dos atributos considerados pelos consumidores em seu processo decisório de compra é um fator de competitividade para as organizações, bem como constitui um campo de conhecimento teórico sobre produtos e serviços existentes no mercado. Este trabalho buscou identificar quais são os atributos, e suas respectivas dimensões, considerados pelos consumidores em seu processo decisório para aescolha de restaurantes. Para tal, foram realizados dois estudos, sendo o primeiro um estudo qualitativo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The model consists of the following steps: recognition of the need, search for information, evaluation of alternatives, purchase, consumption, post-purchase assessment and discard. Several authors have used this model in their papers on consumer behaviour in diverse economic sectors and activities, such as the automotive sector (Bevilacqua, 2013), coffee production (Silva et al, 2014), supermarkets (Moreira et al, 2013), mobile communications (Sata, 2013), group buying (Dias et al, 2014) and, finally, restaurants (Lima Filho et al, 2014;Azevedo et al, 2017;Loriato and Pelissari, 2017;Pedraja Iglesias and Jesus Yagüe Guillén, 2004).…”
Section: Theoretical-analytical Backgroundmentioning
confidence: 99%
“…The model consists of the following steps: recognition of the need, search for information, evaluation of alternatives, purchase, consumption, post-purchase assessment and discard. Several authors have used this model in their papers on consumer behaviour in diverse economic sectors and activities, such as the automotive sector (Bevilacqua, 2013), coffee production (Silva et al, 2014), supermarkets (Moreira et al, 2013), mobile communications (Sata, 2013), group buying (Dias et al, 2014) and, finally, restaurants (Lima Filho et al, 2014;Azevedo et al, 2017;Loriato and Pelissari, 2017;Pedraja Iglesias and Jesus Yagüe Guillén, 2004).…”
Section: Theoretical-analytical Backgroundmentioning
confidence: 99%
“…The analysis of the mean values for the attributes considered important in the decision-making process of restaurant selection indicated that the most important attribute for respondents is the “cleanliness of spaces”, which is a finding supported by other research [5,6,36,38,40,59,60,61,62], and is followed by food made from “fresh ingredients (not frozen)” [5,31]. Therefore, unlike other studies, which place “food quality” on the first rank when it comes to a restaurant selection (an intrinsic attribute) [10,11,12,13,14,29,30,31,32,33,34], Romanian consumers in Cluj-Napoca pay much more attention to “cleanliness of spaces” (an extrinsic attribute). Other important attributes were found to be the “ambiance” and the “variety of the menu”.…”
Section: Discussionmentioning
confidence: 61%
“…Among the internal features, food quality is considered a crucial factor of influence in the selection process of a restaurant [10,11,12,13,29,30,31,32] and a predictor of customer satisfaction [14,33,34]. It consists of two dimensions: organoleptic and presentation [12]. However, a study conducted on full service restaurants highlights that customers have greater expectations that exceed food quality by focusing on the quality of the service [15].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations